DOES VITAMIN D DEFICIENCY CONTRIBUTE TO THE SEVERITY OF ASTHMA IN CHILDREN AND ADULTS? - Ahmed, Syed Zaryab; Jaleel, Anila; Hameed, Kamran; Qazi, Salman; Suleman, Ahsan (Journal of Ayub Medical College Abbottabad, 2015)
Role of vitamin D in the health of bones has been well established for over decades. It was known that its deficiency caused rickets in children and osteomalacia in adults. Later it was discovered that these can be corrected by giving vitamin D. Researchers discovered that vitamin D can be synthesized by exposure to sun. Hence it was also named "the sunshine vitamin". As time passed it was observed that low levels of vitamin D were associated with multiple diseases. This sparked the interest of the scientific community to further the research on vitamin D which led to the studies that started associating vitamin D with various diseases like cancers (prostate, colon and breast), autoimmune diseases (rheumatoid arthritis), infectious diseases (tuberculosis, hepatitis B, hepatitis C, HIV), cardiovascular diseases, mental illnesses (schizophrenia), diabetes mellitus (type 1, type 2 and gestational) and allergic conditions like asthma. With time, more studies were carried out relating levels of vitamin D to development of asthma, asthma exacerbations and risk factors leading to development of asthma like respiratory tract infections with positive associations. A number of studies were carried out which tried to explain the possible molecular mechanisms relating deficiency of vitamin D in pathogenesis of asthma. This review summarizes the role of vitamin D in development of asthma and probable mechanisms relating vitamin D to the pathogenesis of asthma. Keywords: Asthma, Vitamin D, allergic disease